2021
DOI: 10.3389/fcvm.2021.735008
|View full text |Cite
|
Sign up to set email alerts
|

Virtual (Computed) Fractional Flow Reserve: Future Role in Acute Coronary Syndromes

Abstract: The current management of acute coronary syndromes (ACS) is with an invasive strategy to guide treatment. However, identifying the lesions which are physiologically significant can be challenging. Non-invasive imaging is generally not appropriate or timely in the acute setting, so the decision is generally based upon visual assessment of the angiogram, supplemented in a small minority by invasive pressure wire studies using fractional flow reserve (FFR) or related indices. Whilst pressure wire usage is slowly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 82 publications
1
5
1
Order By: Relevance
“…The presented findings, although preliminary, constitute another step forward in the development of virtual PCI planning tools. Our study extends prior observations from computed tomography coronary angiography (CCTA) based FFRCT PCI planning software [ 27 ] and other angiography-derived residual FFR indices [ 25 , 28 , 29 , 30 ]. These tools have the potential to improve treatment qualification by better predicting which patients end with proper functional PCI outcomes as well as those with a lower likelihood of functionally satisfactory outcome, and thus, a risk of a futile invasive procedure.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…The presented findings, although preliminary, constitute another step forward in the development of virtual PCI planning tools. Our study extends prior observations from computed tomography coronary angiography (CCTA) based FFRCT PCI planning software [ 27 ] and other angiography-derived residual FFR indices [ 25 , 28 , 29 , 30 ]. These tools have the potential to improve treatment qualification by better predicting which patients end with proper functional PCI outcomes as well as those with a lower likelihood of functionally satisfactory outcome, and thus, a risk of a futile invasive procedure.…”
Section: Discussionsupporting
confidence: 81%
“…As a next step, the ability to predict the functional outcomes of PCI is gaining increased attention [ 27 , 28 , 29 , 30 ]. Recent developments in the vFFR software allowed us to simulate the effect of ‘virtual’ PCI and estimate post-PCI FFR (residual vFFR).…”
Section: Introductionmentioning
confidence: 99%
“…We included in our study 40 patients affected by ACS at the time of revascularization confirming the usefulness of vFFR in ACS patients. 25 The rate of RIMA graft occlusion in our study was higher than the reported rate in the literature (68 vs. 89%, respectively) that could be explained by differences in surgical technique (such as Y-grafting). 26 In our previous study, we studied 70 consecutive patients treated with CABG who underwent clinically indicated ICA after surgery with the aim of investigating the functional progression of CAD in native vessels and assessing the relationship between the preoperative angiography-derived FFR value and graft occlusion.…”
Section: Discussioncontrasting
confidence: 75%
“…Identifying the lesions which are physiologically significant in ACS patients can be challenging. We included in our study 40 patients affected by ACS at the time of revascularization confirming the usefulness of vFFR in ACS patients 25 …”
Section: Discussionmentioning
confidence: 79%
“…Correct calculation of angiography-derived FFR critically depends on the operator's experience. It is demonstrated that when an expert reanalysis previous 3D reconstruction of casual users, it may result in a change in the treatment decision in as much as 37% of cases ( 52 ).…”
Section: Limitations Of Fractional Flow Reserve Derived From Invasive...mentioning
confidence: 99%